Solitary extramedullary plasmacytoma of the penis - Scarberry, Kyle (Medknow Publications & Media Pvt Ltd, 2014)
Solitary extramedullary plasmacytomas are rare plasma cell malignancies, particularly outside the upper aerodigestive tract. A 90-year-old male presented with a penile mass suspicious for penile carcinoma. Pathology revealed the tumor to be an Epstein-Barr virus-associated plasmacytoma with no radiographic evidence of bone or other soft tissue involvement. There was no laboratory evidence of multiple myeloma.